STRENGTH TRAINING FOR BASKETBALL, ACCORGING TO GAME MODEL - Cuzzolini, Francesco (Sport- és Egészségtudományi füzetek, 2025)
During his plenary lecture, Francesco Cuzzolin discussed the transition from scientific knowledge to practical application, with a specific focus on strength training for basketball players.